The interplay between green policy, electricity prices, financial constraints and jobs: Firm-level evidence - Gert Bijnens; John Hutchinson; Jozef Konings; Arthur Saint Guilhem (European Central Bank (ECB), 2021)
Increased investment in clean electricity generation or the introduction of a carbon tax will most likely lead to higher electricity prices. We examine the effect from changing electricity prices on manufacturing employment. Analyzing firm-level data, we find that rising electricity prices lead to a negative impact on labor demand and investment in sectors most reliant on electricity as an input factor. Since these sectors are unevenly spread across countries and regions, the labor impact will also be unevenly spread with the highest impact in Southern Germany and Northern Italy. We also identify an additional channel that leads to heterogeneous responses. When electricity prices rise, financially constrained firms reduce employment more than less constrained firms. This implies a potentially mitigating role for monetary policy.
Keywords: E52; H23; J23; Q48; 330; environmental regulation; labor demand; employment; manufacturing industry; monetary policy